Development of rainfall temporal pattern in Kuantan River Basin - Siti Nadirah, Omar (2017)
Malaysia is located at equatorial region which having hot and humid climate through all year. Malaysia will also be having two monsoons which cause a heavy and frequent rain during that period of time. Due to the extreme rainfall, the land is easily flooding. Rainfall temporal pattern is used in designing hydraulic and hydrology structures as in Manual Saliran Mesra Alam Malaysia 2 (MSMA 2). However, MSMA 2’s temporal pattern are develop based on region. In this study, the temporal pattern is developed based on stations at Kuantan River Basin. The objectives of the study are to develop Rainfall Temporal Pattern for Kuantan River Basin using Huff Time Distribution Method and WRRI Method and also to compare the result obtained between Huff Time Distribution Method (HTDM) and WRRI Method. The rainfalls are categorized for 60 minutes, 120 minutes and 180 minutes event. Each event are divided to four quartiles and calculated in accordance with Huff Time Method to produce the temporal pattern. While WRRI Method, the events are first rearrange so that the highest depth of rain is set at the middle of storm duration. The analysis is run for both method and compared in terms of percentage. There was a differences in the temporal pattern developed. Based on the analysis of the rainfall temporal pattern developed by HTDM and WRRI method, the differences in each graph plotted varies from about 2% to 57%. The highest percentage of differences of the three events is 56.68% and the lowest is 2.54%.